Recent Insights on the Maternal Microbiota: Impact on Pregnancy Outcomes - Di Simone, Nicoletta; Santamaria Ortiz, Amparo; Specchia, Monia; Tersigni, Chiara; Villa, Paola; Gasbarrini, Antonio; Scambia, Giovanni; D’Ippolito, Silvia (Frontiers in Immunology, 2020)
Hormonal changes during and after pregnancy are linked with modifications in the maternal microbiota. In our manuscript, we describe the importance of maternal microbiota in pregnancy and we examine whether changes in maternal microbial composition at different body sites may have an association with pregnancy complications. We also analyze the likely interactions between microbiota and immune system. Gastrointestinal (Gut) Microbiota. During pregnancy, microbiota undergoes profound changes, leading to an increase in lactic acid-producing bacteria and a reduction in butyrate-producing bacteria. The meaning of such changes still remains to be clarified. Additionally, various studies have indicated a possible involvement of maternal gut microbiota in autoimmune and life-long diseases. Vaginal Microbiota. The human vagina has its own microbiota; changes of the vaginal microbiota seem to be related to a number of pregnancy complications. Recent studies have shown reduced Lactobacilli, an increased bacterial diversity, and low vaginal levels of β-defensin-2 in patients with preterm birth (PTB). In contrast, early and healthy pregnancies are characterized by low diversity and low numbers of bacterial communities dominated by Lactobacillus. These observations may suggest that early vaginal cultures, that show absence of Lactobacillus and a polymicrobial vaginal colonization, are risk factors for PTB. Endometrial microbiota. Endometrium is not a sterile site: it has only been in recent years that resident endometrial microbiota has been defined. Questions remain however around what the main components of endometrial microbiota are and their impact on reproductive tract, in terms of both fertility and pregnancy outcomes. A classification based on endometrial bacterial patterns would help develop a microbiota-based diagnosis, personalized therapies for prevention of obstetrical complications and personalized treatments through nutritional, microbial, or pharmaceutical interventions.